PENGARUH STRUKTUR PASAR TERHADAP KINERJA PERBANKAN DI INDONESIA - sofriza Syofyan (Media Riset Bisnis & Manajemen, 2002)
The paper discusses the banking perfomance which argues thatalways has the relation with the influence of concentration ratio profitability and influence the aset quantity profitability, cr influence of the efficiency the performance. The objective of this research is to examine how strong the influence of market structure in banking performance. Based on statistic result, there are fact that banking performance in Indonesia has been influenced by market structure and capital of the bank.